Toma Loa Se Banari: A Cultural Concept for Improving Employee Resources and Company Performance in Tidore Islands City PDAM - Yusuf Kamis; Budiyanto Budiyanto; Suwitho Suwitho (Cita Konsultindo Research Center, 2024)
The effectiveness of government's regional drinking water company (PDAM) in Tidore Islands City depends heavily on the quality of its human resources, which is critical for overcoming challenges and capitalizing on opportunities. The purpose of this study is to investigate the difficulties faced by PDAM in Tidore Islands City concerning the quality of their human resources and service delivery. The study suggests strategies for enhancing human resource development and promoting a culture of integrity to improve organizational efficiency and customer satisfaction. This study employs a qualitative, descriptive methodology. Integrating the PDCA concept and model in human resource development at the Tidore Islands City PDAM has substantially improved training procedures, assessment, and evaluation. However, some areas require further development, particularly in aligning training activities with organizational objectives and addressing policy implementation gaps. Training initiatives, guided by the toma loa se banari culture, aim to improve employee competence, professionalism, and service quality, emphasizing the significance of ongoing training to meet changing company needs and ensure quality service delivery.